DURABILITY OF CERAMIC-MATRIX COMPOSITES - LONGBIAO, LI (Woodhead Publishing Series in Composites Science and Engineering Ser., 2020)
Durability of Ceramic-Matrix Composites presents the latest information on these high-temperature structural materials and their outstanding advantages over more conventional materials, including their high specific strength, high specific modulus, high temperature resistance and good thermal stability. The critical nature of the application of these advanced materials makes it necessary to have a complete understanding of their characterization. This book focuses explicitly on the durability of CMCs and will be extremely valuable for materials scientists and engineers who are dealing with the simulation of durability response and fatigue of ceramic matrix composites.